Respuesta :
Answer:
(C) Multiply the bottom equation by 2.
Step-by-step explanation:
The given equation are:
[tex]3x+4y=8[/tex] (1)
and [tex]6x-2y=9[/tex] (2)
Now, in order to add these equations and eliminate y, we should multiply the bottom equation by 2, thus we have
[tex]3x+4y=8[/tex] (3)
[tex]12x-4y=18[/tex] (4)
Now, adding the above equations, we have
[tex]15x=26[/tex]
[tex]x=\frac{26}{15}[/tex]
Now, substituting the value of x in equation (3), we have
[tex]3(\frac{26}{15})+4y=8[/tex]
[tex]y=\frac{7}{10}[/tex]
Therefore, option (C) is correct.